2004
DOI: 10.1073/pnas.0306294101
|View full text |Cite
|
Sign up to set email alerts
|

Tapasin enhances MHC class I peptide presentation according to peptide half-life

Abstract: Understanding how peptides are selected for presentation by MHC class I is crucial to vaccination strategies based on cytotoxic T lymphocyte priming. We have studied this selection of the MHC class I peptide repertoire in terms of the presentation of a series of individual peptides with a wide range of binding to MHC class I. This series was expressed as minigenes, and the presentation of each peptide variant was determined with the same MHC class I peptide-specific antibody. In wild-type cells, the hierarchy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
164
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(173 citation statements)
references
References 45 publications
7
164
1
1
Order By: Relevance
“…Having analyzed the peptide repertoire presented by MHC-I on the cell surface, a previous study suggested that tapasin controls the peptide repertoire, resulting in the presentation of more stable peptide-MHC-I complexes (28). At first glance, our finding that the Tpn 1-87 facilitation was high for unstable peptide-HLA-A*02:01 complexes seems to contradict the suggested role of tapasin as a mediator of cell surface expression of stable peptide-HLA-I complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Having analyzed the peptide repertoire presented by MHC-I on the cell surface, a previous study suggested that tapasin controls the peptide repertoire, resulting in the presentation of more stable peptide-MHC-I complexes (28). At first glance, our finding that the Tpn 1-87 facilitation was high for unstable peptide-HLA-A*02:01 complexes seems to contradict the suggested role of tapasin as a mediator of cell surface expression of stable peptide-HLA-I complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Tapasin simultaneously binds to peptide-receptive MHC class I heterodimers and to TAP, localizing MHC class I to a concentrated source of newly degraded antigenic peptides (1)(2)(3)(4)(5). There is also evidence that tapasin optimizes or edits the peptides presented on MHC class I by facilitating exchange of suboptimal peptides for higher-affinity cargo (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…2A), that contains an altered OVA peptide ligand SIINYEKL, which binds to K b with a 1,000-fold lower affinity compared with the WT peptide Fig. S3) (16). To test whether this altered peptide from the SCT could be cross-presented, we immunized mice with DNA vaccines with the keratinocyte-specific K14 promoter (17) driving expression of cDNA or SCT constructs corresponding to either WT OVA or the mutant SIINYEKL sequence (Fig.…”
Section: Resultsmentioning
confidence: 99%